Renal Replacement Therapy Tactics in Russian Regions with an Average Population Density - D. V. Perlin (Вестник урологии, 2020)
The lecture details the current understanding of renal replacement therapy and current advances in this field. The current diagnostic and treatment algorithms have been clarified, allowing timely assistance to the population with chronic kidney disease. I tried to identify the main milestones on the way to increasing the availability of renal replacement therapy in our country, where many regions have a very large area and low population density. Obviously, much effort remains to be done to achieve a good level of security and accessibility of renal replacement therapy for our population. I hope that this manuscript will serve to some extent the aims that have been set.The study did not have sponsorship. The author has declared no conflicts of interest